Pelatihan dan Pendampingan Microsoft Excel untuk Meningkatkan Keahlian Staff Desa Tanjung Baru - Azwar, Azwar; Lucyana, Lucyana; Destiarini, Destiarini; Meiwinda, Eka Rizki; Hasibuan, Rahmawaty (Universitas Dehasen Bengkulu, 2025)
Computer technology has developed recently and is used to help humans, one of the technologies is the use of the Microsoft Excel computer application. A village is a legal community unit that has territorial boundaries and has the authority to regulate and manage community interests and is led by the village head or village head. The use of Microsoft Excel has been used to process data but it is not fully known so it does not provide benefits and is less effective in serving the community. The aim of this training is to improve the quality of human resources in the Tanjung Baru village apparatus. The methods used are interviews and surveys. The results obtained from this training are an increase in the ability of Tanjung Baru village equipment and staff in operating Microsoft Excel to help smooth work and village administration services